PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS KONSUMEN DALAM PENGGUNAAN JASA PENGIRIMAN BARANG - Marla S. Ratunara; Victor R. Pattipeilohy; Frangky Jansen Louth (Jurnal Administrasi Terapan, 2026)
This research aims to analyze the influence of trust and satisfaction on consumer loyalty to Shopee express. As one of the delivery services available in Indonesia. However, the reality is that there are still complaints from consumers regarding the performance of Shopee express employees, such as delays in the delivery time of ordered goods, failure to confirm the arrival of goods to consumers before delivery, refusal to accept complaints from consumers regarding the delivery service, and frequently asking consumers to pick up their goods themselves at the Shopee express office. This research uses a quantitative approach with data collected through questionnaires distributed to Shopee express users. Data analysis employs multiple linear regression to test the influence of independent variables (trust and satisfaction) on the dependent variable (consumer loyalty).The research results show that trust has a positive and significant effect on confidence with a regression coefficient of 0.000 (p < 0.05), and satisfaction has a positive and significant effect with a regression coefficient of 0.000 (p < 0.05). To improve this, companies need to optimize operational systems, enhance transparency, and train staff in honesty and professionalism. Focus on improving delivery reliability and service responsiveness.